Analisis Penerapan Good Corporate Governance (GCG) oleh PT Garuda Indonesia (Persero) Tbk dalam Masa Penundaan Kewajiban Pembayaran Utang (PKPU) - Anwar Hafidz Amrullah; Alfi Taufiq Asyidqi; Joshua Suwandi; Anggun Ratna Alifa; Nur Gita Oktaviani; Nyulistiowati Suryanti (Bulletin of Community Engagement, 2024)
PT Garuda Indonesia (Persero) Tbk is one of the State-Owned Enterprises that has passed the postponement of debt payment obligations (PKPU) period well until it escaped the threat of bankruptcy. The escape of PT Garuda Indonesia from the threat of bankruptcy is inseparable from its success in applying the principles known in Good Corporate Governance (GCG). This research uses a normative method with a statutory approach, and with the specification of this research using an analytical descriptive method. The result of this research is that PT Garuda Indonesia managed to recover its company and show positive growth, maintaining its role as a national airline with more stable operational sustainability through the sustainable implementation of GCG principles of Transparency, and Accountability. The GCG principles also not only play an important role in efforts to save the company from bankruptcy, but also forever